Metode Penyelesaian dalam Kajian Matan Hadis-hadis Kontroversial - Rahman, Abd (Jurnal Adabiyah, 2010)
This writing discusses controversial hadits and the way of understanding the hadis, using various methods and interpretation technique. Although a hadis is recognized controversial, it doesn’t mean that it cannot be solved. Some ulamas of hadis have discussed and put forward some alternative arguments to come to final conclusion. Some methods such as; ei-Jem’u, al-Tarjih, al Nasikh, wa al-Mansukh dan al-Tauqif, as well as textual, contextual interpretation, linguistic or historical approach can be regarded as ways to understand the essentian meaning of the controversial had is.